Partial Substitution of Fish Meal with Soy Protein Concentrate on Growth, Liver Health, Intestinal Morphology, and Microbiota in Juvenile Large Yellow Croaker (Larimichthys crocea) - Xuexi Wang; Hongjie Luo; Dejuan Wang; Yunzong Zheng; Wenbo Zhu; Weini Zhang; Zhengbang Chen; Xinhua Chen; Jianchun Shao (Aquaculture Nutrition)
The present study investigated the growth performance, feed utilization, intestinal morphology, and microbiota communities of juvenile large yellow croaker (Larimichthys crocea) fed diets containing different proportions of soy protein concentrate (SPC) (0, 15%, 30%, and 45%, namely FM, SPC15, SPC30, and SPC45) as a substitute for fish meal (FM) for 8 weeks. The weight gain (WG) and specific growth rate (SGR) in fish fed SPC45 were significantly lower than those fed FM and SPC15 but not differ with these fed SPC30. The feed efficiency (FE) and protein efficiency ratio (PER) decreased sharply when the dietary SPC inclusion level was higher than 15%. The activity of alanine aminotransferase (ALT) and expression of alt and aspartate aminotransferase (ast) were significantly higher in fish fed SPC45 than those fed FM. The activity and mRNA expression of acid phosphatase were opposite. The villi height (VH) in distal intestine (DI) showed a significant quadratic response to increasing dietary SPC inclusion levels and was highest in SPC15. The VH in proximal intestine, middle intestine decreased significantly with increasing dietary SPC levels. The 16S rRNA sequences in intestine revealed that fish fed SPC15 had higher bacterial diversity and abundance of Phylum Firmicutes such as order Lactobacillales and order Rhizobiaceae than those fed other diets. Genus vibrio, family Vibrionaceae and order Vibrionales within phylum Proteobacteria were enriched in fish fed FM and SPC30 diets. Tyzzerella and Shewanella that belongs to phylum Firmicutes and Proteobacteria, respectively, were enriched in fish fed SPC45 diet. Our results indicated that SPC replacing more than 30% FM could lead to lower quality diet, retard growth performance, ill health, disordered intestine structure, and microbiota communities. Tyzzerella could be the bacteria indicator of intestinal in large yellow croaker fed low quality diet due to high SPC content. Based on the quadratic regression analysis of WG, the best growth performance could be observed when the replacement of FM with SPC was 9.75%.